2018
DOI: 10.1016/j.xphs.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Loading of Sodium Lauryl Sulfate and Fasted State Simulated Intestinal Fluid Micelles Within the Diffusion Layers of Dispersed Drug Particles During Dissolution

Abstract: Poorly water soluble drug candidates have been common in developmental pipelines over the last several decades. This has fueled considerable research around understanding how bile salt and model micelles can improve drug particle dissolution rates and human drug exposure levels. However, in the pharmaceutical context only a single mechanism of how micelles load solute has been assumed, that being the direct loading mechanism put forth by Cussler and coworkers (Am Inst Chem Eng J. 1976;22(6):1006-1012) 40 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…We conclude that the IDR values in biorelevant media that contain phospholipids and taurocholate depend strongly on partitioning into formed micelles, and that this partitioning depends on lipophilicity and ionization. In fact, these considerations align with the recently proposed indirect loading mechanism of dissolving drug molecules into FaSSIF micelles [65,66], which suggests that the equilibrium partition coefficient of the API between the micellar phase and the buffer phase can prevent dissolved drug molecules from loading a micelle up to its equilibrium saturated value. This results in slower dissolution rates than predicted by the Noyes-Whitney equation, and has been observed experimentally for danazol in FaSSIF [60,65].…”
Section: Impact Of Physicochemical Properties On Idrsupporting
confidence: 76%
See 1 more Smart Citation
“…We conclude that the IDR values in biorelevant media that contain phospholipids and taurocholate depend strongly on partitioning into formed micelles, and that this partitioning depends on lipophilicity and ionization. In fact, these considerations align with the recently proposed indirect loading mechanism of dissolving drug molecules into FaSSIF micelles [65,66], which suggests that the equilibrium partition coefficient of the API between the micellar phase and the buffer phase can prevent dissolved drug molecules from loading a micelle up to its equilibrium saturated value. This results in slower dissolution rates than predicted by the Noyes-Whitney equation, and has been observed experimentally for danazol in FaSSIF [60,65].…”
Section: Impact Of Physicochemical Properties On Idrsupporting
confidence: 76%
“…In fact, these considerations align with the recently proposed indirect loading mechanism of dissolving drug molecules into FaSSIF micelles [65,66], which suggests that the equilibrium partition coefficient of the API between the micellar phase and the buffer phase can prevent dissolved drug molecules from loading a micelle up to its equilibrium saturated value. This results in slower dissolution rates than predicted by the Noyes-Whitney equation, and has been observed experimentally for danazol in FaSSIF [60,65]. Clearly, further exploration of molecular properties important for IDR would benefit from computational modeling of dissolution, which would require even larger datasets than the one established here.…”
Section: Impact Of Physicochemical Properties On Idrsupporting
confidence: 76%
“…This difference in transport rates results in the formation of a concentration gradient from the bulk solution to the membrane surface, where the thickness of the concentration gradient depends on the hydrodynamic conditions of the system. However, it has been reported that the addition of micelles may improve the overall mass transport of drug molecules across the ABL, resulting in increased local drug activity at the membrane surface. Similar observations have been made in systems containing other colloidal species and in systems containing an excess of crystalline drug . The term “particle drifting”, coined by Sugano, describes this phenomenon in systems containing excess nanocrystalline particles drifting into the mucus and water boundary layers .…”
Section: Introductionmentioning
confidence: 70%
“…In cases where the API is a PWSD, the systemic absorption of the API is often limited by its diffusion through the aqueous boundary layer (ABL) within the small intestinal lumen. Several papers have reported the benefits in permeability gained from the encapsulation of the API in nanoscale encapsulating species because of the combined diffusivity of freely solubilized drugs and encapsulated drugs in nanoscale species. However, it is essential to note that the benefits of the permeability of ABL-limited APIs because of particle drifting are largely seen when the encapsulating species are smaller than 50 nm. Therefore, small changes in size (1–5 nm) will significantly impact the particle drifting observed.…”
Section: Discussionmentioning
confidence: 99%